The past in the past and the present: a study of deep time and the city. (October 2020) - Stewart, Edward
Abstract : Cities have an immortal quality in the minds of their inhabitants, enduring over the span of their lifetimes, ever changing yet familiar as every new stratigraphic relationship in the city's fabric is thrust, hacked or crammed into the centuries and millennia of anthropogenic stratum that shaped the place to that point. What role does this deep time play in the lives of the shoppers, commuters, dwellers, and workers who interact with the largely invisible urban prehistoric landscape? This paper reports on experiential landscape research focused on a possible prehistoric site in Glasgow, the Camphill enclosure, in Queen's Park. An account of the site has been provided detailing the academic histories from antiquarian rediscovery to the present, current interactions, and a phenomenology-based interpretative narrative of past. The paper concludes with a critique of the research undertaken highlighting the limitations of both the methods and practices and some thoughts on deep time in urban places.